Adherence to treatment in patients with cerebrovascular disease as a multifactorial problem - M. M. Tanashyan; K. V. Antonova; O. V. Lagoda; A. A. Kornilova; E. P. Shchukina (Неврология, нейропсихиатрия, психосоматика, 2023)
The most important component of the treatment effectiveness is the adherence of patients to the recommendations of the attending physician, which can affect the course and prognosis of the disease. The problem of adherence in cerebrovascular disease (CVD), depending on the clinical picture of the disease and comorbid diseases, is currently poorly studied.Objective: to assess the degree of adherence to treatment in patients with the main diagnosis of CVD and to determine the factors influencing it.Material and methods. 161 patients with cerebrovascular pathology aged 58–70 years (mean age 64 years) were examined. The assessment of somatic and neurological status, neuropsychological examination, assessment of adherence to therapy using standardized national questionnaires: the Russian Scale of Quantitative Assessment Adherence to Treatment (QAA-25) and the Domestic Therapy Adherence Questionnaire (DTAQ), laboratory studies were performed. The influence of cognitive impairments (CI), background and comorbidities, as well as drug therapy in the framework of the prevention of cardiovascular diseases were evaluated.Results. In patients with CVD, according to the results of the QAA-25 questionnaire, adherence to medical support was 33.4 [26.3; 57.5] %, drug therapy – 44.4 [29.7; 59.0] %, the lifestyle modifications – 31 [26; 55] %, overall adherence to treatment – 31 [26; 56] %. The proportion of patients with low adherence according to the DTAQ test reached 19.9%. In patients with a low adherence, the result on the Montreal Cognitive Assessment Test (MoCA) was 21 points, in patients with very high adherence – 26 points. An increase in the total number of prescribed basic drugs was accompanied by a decrease in adherence according to the results of DTAQ (p=0.041) and QAA-25 (p<0.05) tests. The worst indicators of adherence were noted in CI and the presence of such factors as arterial hypertension (AH), an increase in waist circumference, the severity of carbohydrate metabolism disorders, especially the combination of AH and type 2 diabetes mellitus (DM).Conclusion. The conducted study demonstrated insufficient adherence to treatment in patients with chronic CVD. Adherence deterioration factors are CI, an increase in the number of drugs administered, comorbid diseases, of which the combination of AH and type 2 DM is of the greatest importance.